2009
DOI: 10.1590/s0074-02762009000600002
|View full text |Cite
|
Sign up to set email alerts
|

Larvicidal activity of extracts from three Plumbago spp against Anopheles gambiae

Abstract: Three Plumbago spp have been tested for mosquito larvicidal activity. The crude extracts exhibiting the highest larvicidal activity against Anopheles gambiae were hexane (LC 50 = 6.4 µg/mL)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 13 publications
2
17
0
2
Order By: Relevance
“…Nilai LC 50 larva instar II, III, dan IV berturut-turut 0,0154, 0,0164, dan 0,0274 µ g/ml. Untuk spesies nyamuk lain, yaitu A. gambiae, nilai LC 50 dan LC 90 ekstrak heksan daun encok berturut-turut ialah 6,4 dan 26,2 µg/ml (Maniafu et al 2009). Perbedaan nilai LC 50 ekstrak heksan daun encok terhadap larva A. aegypti dan A. gambiae cukup besar karena aktivitas larvasidal yang berasal dari ekstrak tanaman sangat bervariasi, bergantung pada faktor dalam dan luar tanaman.…”
Section: Daun Encok Sebagai Insektisidaunclassified
See 1 more Smart Citation
“…Nilai LC 50 larva instar II, III, dan IV berturut-turut 0,0154, 0,0164, dan 0,0274 µ g/ml. Untuk spesies nyamuk lain, yaitu A. gambiae, nilai LC 50 dan LC 90 ekstrak heksan daun encok berturut-turut ialah 6,4 dan 26,2 µg/ml (Maniafu et al 2009). Perbedaan nilai LC 50 ekstrak heksan daun encok terhadap larva A. aegypti dan A. gambiae cukup besar karena aktivitas larvasidal yang berasal dari ekstrak tanaman sangat bervariasi, bergantung pada faktor dalam dan luar tanaman.…”
Section: Daun Encok Sebagai Insektisidaunclassified
“…Faktor dari dalam yaitu spesies, bagian tanaman yang digunakan, dan umur tanaman. Faktor dari luar meliputi metode aplikasi, asal tanaman, dan teknik budi daya (Dadang dan Prijono 2008; Maniafu et al 2009). …”
Section: Daun Encok Sebagai Insektisidaunclassified
“…In a search for larvacidal activity one study found β-sitosterol (17-(5-Ethyl-6-methylheptan-2-yl)-10,13-dimethyl-2, 3,4,7,8,9,11,12,14,15,16,17 dodecahydro-1H cyclopenta [a]phenanthren-3-ol) and plumbagin. The study had utilized column chromatography and1D, 2D NMR to find out these compounds [12].…”
Section: Chemistry Of Plumbago Zeylanica Lmentioning
confidence: 99%
“…The study had utilized column chromatography and1D, 2D NMR to find out these compounds [12]. Also another journal intended at evaluating the anti-inflammatory and cytotoxic effects of extract from Plumbago zeylanica found out beta-sitosterol and gugultetrol-18-ferrulate with the help of silica gel column chromatography, high performance liquid chromatography (HPLC) and proton and carbon nuclear magnetic resonance spectroscopy analysis (1H and 13C NMR), Infra red and mass spectroscopy.…”
Section: Chemistry Of Plumbago Zeylanica Lmentioning
confidence: 99%
“…The naphthoquinone, plumbagin (197) isolated from Plumbago zeylanica ) and other plant species (Mishra et al 2010a;Mishra et al 2010b;Mishra and Tiwari 2011) exhibit larvicidal activity against An. gambiae with LC 50 value of 1.9 μg/mL (Maniafu et al 2009;Adikaram et al 2002) (Michaelakis et al 2009). However, it is difficult to discuss the SAR criteria responsible for the mosquitocidal activities in this set of compounds, presence of reduced quinine ring (ring B), hydroxyl group at C-4 and methyl group at C-3 appears to be important in imparting the mosquitocidal activity compared to others.…”
Section: Carboline Alkaloidsmentioning
confidence: 99%